Kualifikasi Agen Perubahan Dalam Pengembangan Organisai Di SDN 05 Air Tawar Barat - Nur Azizah (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
Change agents are key elements in organizational processes, particularly in educational settings such as elementary schools. This article examines the essential qualifications that change agents must possess to facilitate effective transformation at SDN 05 Air Tawar Barat. Based on change management theory, these qualifications include technical knowledge of education and organization, communication and collaboration skills, leadership and motivational abilities, adaptive analysis, and ethical and sustainable commitment. The implementation of these qualifications at the school has been shown to support innovations such as digitalization of learning and literacy programs, despite the challenges of limited resources. The study findings indicate that qualified change agents can improve the quality of education and student well-being, with implications for sustainable school development. This research encourages further training for change agents to support educational reform.